Catalytic reforming of tar during gasification. Part IV. Changes in the structure of char in the char-supported iron catalyst during reforming - Min, Zhenhua; Zhang, Shu; Yimsiri, P.; Wang, Yi; Asadullah, Mohammad; Li, Chun-Zhu (Elsevier Ltd, 2013)
Our previous parts of this series have shown the char-supported iron catalysts to possess high activity for the reforming of tar during biomass gasification. This study aims to investigate the changes to the structure of char in the char-supported iron catalyst during the reforming of tar derived from the pyrolysis of mallee wood biomass. The char structure was characterised with Raman spectroscopy and its intrinsic reactivity at 400 °C in a thermogravimetric analyser. The results showed that the Raman peak area in the range of 800–1800 cm-1 of the catalysts changed slightly after being used for the steam reforming of biomass tar. The changes in the Raman band area ratio of ID/I(Gr+Vl+Vr) indicated that the relative ratio of larger and smaller aromatic ring systems increased after reforming at temperatures at 800 °C or higher. The changes in the char-air reactivity before and after reforming provided further insights to the changes in char structure as well as the importance of alkali and alkaline earth metallic species deposited on the char-supported catalysts during reforming.